2021
DOI: 10.3390/cells10082150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SGLT2-Inhibitors on Epicardial Adipose Tissue: A Meta-Analysis

Abstract: (1) Sodium–glucose cotransporter-2 inhibitors (SGLT2-i) reduce adipose tissue and cardiovascular events in patients with type 2 diabetes (T2D). Accumulation of epicardial adipose tissue (EAT) is associated with increased cardio-metabolic risks and obstructive coronary disease events in patients with T2D. (2) We performed a systematic review and meta-analysis of SGLT2-i therapy on T2D patients, reporting data on changes in EAT after searching the PubMed/MEDLINE, Embase, Science Direct, Scopus, Google Scholar, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…In one study, dapagliflozin caused a reduction in EAT thickness independent of weight loss [215], perhaps thanks to the improvement of EAT cells' sensitivity to insulin and a reduction in local proinflammatory chemokines secretion [216]. Although SGLT2 inhibitors are relatively new drugs, the first meta-analyses have already confirmed their beneficial impact on EAT [217].…”
Section: Therapeutic Options To Affect Eatmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, dapagliflozin caused a reduction in EAT thickness independent of weight loss [215], perhaps thanks to the improvement of EAT cells' sensitivity to insulin and a reduction in local proinflammatory chemokines secretion [216]. Although SGLT2 inhibitors are relatively new drugs, the first meta-analyses have already confirmed their beneficial impact on EAT [217].…”
Section: Therapeutic Options To Affect Eatmentioning
confidence: 99%
“…Statins anti-inflammatory [160,[162][163][164][165] modulation of EAT [164] ↓ EAT metabolic activity [163] PCSK-9 inhibitors unknown Metformin anti-inflammatory [186,187,[196][197][198]200] ↑ fat oxidation and thermogenesis [193,194] ↓ endothelial dysfunction [195] activation of adenosine monophosphate-activated protein kinase [198,200] Thiazolidinediones anti-inflammatory [190,191,[204][205][206] SGLT2 inhibitors anti-inflammatory [210,217] ↓ endothelial dysfunction [213] stimulation of visceral fat burn [215] ↑ EAT cells sensitivity to insulin [217] GLP-1 agonists ↑ pre-adipocyte differentiation [225] ↑ thermogenesis [226] ↑ adipocyte browning [226] DPP-4 inhibitors anti-inflammatory [231][232][233] downregulation of the receptor for advanced glycation end-products [234] ↑ cyclic adenosine monophosphate/protein kinase A signaling and IL-6 production [235] ↓ ROS generation and intercellular adhesion molecule-1 expression [236] Table 1. Cont.…”
Section: Group Of Drugs Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Several possible hypotheses have been extensively discussed, including reductions in body weight, blood pressure, and heart failure incidence [20]. In previous studies, an SGLT2 inhibitor was shown to decrease the amount of pericardial fat and atrial fibrosis [22,23], which might attenuate the occurrence of atrial fibrillation. Several inflammatory cytokines were also revealed to be modified after SGLT2 inhibitor therapy [24,25], such as the NLRP3 inflammasome, which might reduce the area of cardiac fibrosis.…”
Section: Association Between Sglt2 Inhibitor Treatment and Atrial Fib...mentioning
confidence: 99%
“…For ischemic stroke and myocardial infarction, atherosclerosis of the artery is an important risk factor, and the amount of visceral fat has a significant association with atherosclerosis [29,30]. In previous studies, SGLT2 inhibitor therapy was proven to significantly decrease the amount of visceral fat [22,31]. In addition, SGLT2 inhibitors might also reduce adipose-mediated inflammation and proinflammatory cytokine production [32].…”
Section: Association Between Sglt2 Inhibitor Treatment and Other Card...mentioning
confidence: 99%
“…Of note, body weight loss following SGLT2i treatment has been associated with a lower risk of new-onset AF in patients with T2DM [110]. In addition, meta-analysis suggests that epicardial fat is significantly reduced in T2DM patients with SGLT2-i treatment [111]. While epicardial fat is known to promote AF or VF due to the activation of inflammasome and production of cytokines [38,39,112].…”
Section: Antiarrhythmic Efficacy Of Sglt2 Inhibitorsmentioning
confidence: 99%